2023
DOI: 10.33545/26164485.2023.v7.i1b.733
|View full text |Cite
|
Sign up to set email alerts
|

Homoeopathy and its holistic approach in Oro-dental care: A review

Abstract: Oral disease is a major public problem nowadays. Mainly it's a big burden in lowmiddle economic countries in the world. In India, it's a burning problem due to the huge abuse of sugar & process food consumption. Due to poor hygiene knowledge, lack of dental health policy and huge consumption of tobacco, that is why India is called the "Oral cancer capital". Homeopathy is playing a good intervention role for dental diseases, oral hygiene & it's cost-effective, has no Side-effect, easy to use. In the 18 th centu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In this case report 1 st and 2 nd follow-ups showed not much response but after that, the patient gradually recovered. A clear picture that Lycopodium Clavatum showed a beautiful result upon PASI Score was before treatment 7 and after treatment 0.2 and IHM performs incredibly well, scoring 11 out of 13, according to the Modified Naranjo Criteria [2,47] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this case report 1 st and 2 nd follow-ups showed not much response but after that, the patient gradually recovered. A clear picture that Lycopodium Clavatum showed a beautiful result upon PASI Score was before treatment 7 and after treatment 0.2 and IHM performs incredibly well, scoring 11 out of 13, according to the Modified Naranjo Criteria [2,47] .…”
Section: Discussionmentioning
confidence: 98%
“…Homoeopathy is a unique system of medicine in the modern era [42,47,48] . This case report serves as further evidence that homoeopathic drugs can effectively treat psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used to treat many oral problems, such as gingivitis, abscess of the gums, toothache, and so on. Moreover, it can be used as a dressing for the management of the dry socket of the third molars [ 18 ]. It was used for the first time as an intracanal medicament in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It was used for the first time as an intracanal medicament in the present study. In an in vitro study, it has shown a significant zone of inhibition against strains of Enterococcus faecalis and Streptococcus mutans [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation